Helicity in proton-proton elastic scattering and the spin structure of the pomeron - Ewerz, Carlo; Nachtmann, Otto (Arxiv, 2016)
We discuss different models for the spin structure of the nonperturbative pomeron: scalar, vector, and rank-2 symmetric tensor. The ratio of single-helicity-flip to helicity-conserving amplitudes in polarised high-energy proton-proton elastic scattering, known as the complex r_5 parameter, is calculated for these models. We compare our results to experimental data from the STAR experiment. We show that the spin-0 (scalar) pomeron model is clearly excluded by the data, while the vector pomeron is inconsistent with the rules of quantum field theory. The tensor pomeron is found to be perfectly consistent with the STAR data.
Gesehen am 15.02.2018